Associations of body weight and weight change with cardiovascular events and mortality in patients with coronary heart disease. (July 2018) - Dong, Sheng-Yong; Yan, Shuang-Tong; Wang, Man-Liu; Li, Zhi-Bing; Fang, Lian-Qing; Zeng, Qiang
Abstract: Background and aims: It is recommended that patients with coronary heart disease (CHD) pursue a normal body weight, while the effects of body weight and weight change on prognosis are still controversial. The present study was to assess these effects using a large-scale population with CHD in China. Methods: A total of 5276 patients with CHD were included from Jan 2000 to Dec 2014. Baseline and endpoint weights were measured. Outcomes including mortality and cardiovascular events were obtained. Results: Relative to patients with normal weight, risks for adverse outcomes were lowest in overweight patients and similar in obese patients. Hazard ratios (HRs) and 95% confidence interval (95% CI) for all-cause death were 1.42 (1.06, 1.91) if overweight turned into normal weight and were 2.01 (1.28, 3.16) or 5.33 (2.81, 10.1) if obese turned into overweight or normal weight. Death risk increased with the extent of weight loss and moderate or large weight gain ( p <0.05 for all). Similar results were found when risks for cardiovascular mortality and events were considered. Furthermore, these results remained significant when the patients were stratified by several covariates and even when several definitions of weight change were considered. Conclusions: Obesity did not increase adverse outcome risks in patients with CHD. Both weight loss and weight gain increased adverse outcome risks regardless of baseline body weight. The findings suggest that maintaining a stable weight may be a better strategy for the reduction of risks for cardiovascular outcomes and all-cause death in patients with CHD. Highlights: Obesity did not increase adverse outcome risks in patients with CHD. Being overweight at baseline had a protective effect on outcomes. Adverse event risks increased with the decrease of BMI levels during the follow-up. Weight stability was related to the lowest risks regardless of baseline weight. Both weight loss and weight gain increased adverse outcome risks.